'Towards a unified approach for the determination of the bioaccessibility of organic pollutants'. (May 2015) - Collins, Chris D.; Craggs, Mark; Garcia-Alcega, Sonia; Kademoglou, Katerina; Lowe, Stephen
Abstract: Bioaccessibility studies have been widely used as a research tool to determine the potential human exposure to ingested contaminants. More recently they have been practically applied for soil borne toxic elements. This paper reviews the application of bioaccessibility tests across a range of organic pollutants and contaminated matrices. Important factors are reported to be: the physiological relevance of the test, the components in the gut media, the size fraction chosen for the test and whether it contains a sorptive sink. The bioaccessibility is also a function of the composition of the matrix (e.g. organic carbon content of soils) and the physico-chemical characteristics of the pollutant under test. Despite the widespread use of these tests, there are a large number of formats used and very few validation studies with animal models. We propose a unified format for a bioaccessibility test for organic pollutants. The robustness of this test should first be confirmed through inter laboratory comparison, then tested in-vivo. Highlights: We review the range of bioaccessibility tests used for organic pollutants. We include a range of matrices (soil, dust, food) and pollutants (FRs, PAHs, PCBs, pesticides). We discuss the controls on bioaccessibility i.e. properties of the chemical and composition of the bioaccessibility test. We propose a unified format for a bioaccessibility test for organic pollutants.